Direct intraperitoneal resuscitation with lidocaine, methylene blue and pentoxiphylline combination does not decreases inflammation after intestinal ischemia-reperfusion injury in rats - Gandini,Marco (2016)
ABSTRACT PURPOSE: To evaluate the effects of an intraperitoneal solution of methylene blue (MB), lidocaine and pentoxyphylline (PTX) on intestinal ischemic and reperfusion injury METHODS: Superior mesenteric artery was isolated and clamped in 36 adult male Sprague Dawley rats. After 60 minutes, clamp was removed and a group received intraperitoneally UNITO solution (PTX 25mg/kg + lidocaine 5mg/kg + MB 2mg/kg), while the other group was treated with warm 0.9% NaCl solution. Rats were euthanized 45 min after drug administration. Lung and bowel were collected for histological evaluation (using Park's score) and determination of myeloperoxidase (MPO) and malondialdehyde (MDA) levels. RESULTS: Control samples showed lymphoplasmocytic infiltrate and crypt necrosis of villi. MPO and MDA measurements shown no differences between treated and control groups. CONCLUSION: The combination of lidocaine, methylene blue and pentoxyphylline administered intraperitoneally at the studied dose, did not decreased histological lesion scores and biochemical markers levels in intestinal ischemia/reperfusion injury.